Action research for inclusive education : changing places, changing practice, changing minds - Armstrong, Felicity; Moore, Michele, 1962- (RoutledgeFalmer, 2004)
This book presents and discusses an approach to action research to help reverse discriminatory and exclusionary practices in education. Insider accounts of action research will help challenge assumptions about the limits of inclusive education, and offer examples of how change can be realistically achieved through processes of collaboration and participation. Written by a team of practitioner researchers drawn from a wide range of schools and services, this book addresses a wide range of real-life situations by exploring ways in which teachers have tackled inequalities in the school environment.